Metabolic Evaluation in Patients With Hepatitis C Treated With Direct Antiviral Agents - Estefan, Sergio; Brandão-Melo, Carlos Eduardo; dos Santos Silva, Cintia Marques; Gomes, Danilo Cosme Klein; Cardoso, Paula; Costa, Marcia Helena S. (Frontiers in Medicine, 2021)
Epidemiological data clearly indicate a link between hepatitis C virus (HCV) and altered glucose homeostasis. Objective: To evaluate the response of treatment with direct antiviral agents (DAAs) on metabolic variables of patients with hepatitis C. Methods: Observational, cross-sectional study in a sample of patients with hepatitis C starting therapy with DAAs followed on the hepatology division of Federal University of Rio de Janeiro State. Data were collected in two stages; before the start of therapy and between 12 to 52 weeks after obtaining the sustained virological response. Results: In the baseline assessment of the 97 patients selected, 19.3% were obese, 38.6% were overweight, 50% were hypertensive, 43.8% pre-diabetic, 12.5% diabetic, 31.2% dyslipidemic and 21.8 % had metabolic syndrome. There was an increase in total cholesterol and LDL levels (p <0.001), and a non-significant reduction in blood glucose, glycated hemoglobin, insulin and HOMA-IR levels after treatment. In the post-treatment, there was a reduction in fibrosis (p = 0.016), with a reduction in the levels of GGT, AST, ALT (all with p <0.001), as well as in the FIB4 and APRI scores (both with p <0.001) and in the degree of fibrosis evaluated by elastography represented in kPa (p = 0.006). The blood glucose level was higher in patients with steatosis (p = 0.039) after treatment. There was a positive pre-treatment correlation between the degree of fibrosis (kPa) and FIB4 (r = 0.319, p = 0.004), APRI (r = 0.287, p = 0.010) and the NAFLD score (r = 0.275, p = 0.016). Conclusion: Patients with hepatitis C had a high prevalence of metabolic disturbance in the pre-treatment phase, but the therapy did not show any beneficial effects, especially on glucose metabolism.